2016
DOI: 10.1080/10428194.2016.1251592
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance during ibrutinib therapy for chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) in routine clinical practice

Abstract: Due to Cytochrome P450 3A (CYP3A) metabolism, clinical trials of ibrutinib-treated CLL patients prohibited concurrent medications metabolized by CYP3A. We evaluated concomitant medication use in 118 ibrutinib-treated CLL patients outside the context of clinical trials. Seventy-five (64%) patients were on medications that could increase ibrutinib toxicity and 4 (3%) were on drugs that could decrease ibrutinib efficacy. Nineteen (16%) patients were on concomitant CYP3A inhibitors (11 moderate, 8 strong), and 4 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…There are limited data describing physician and patient awareness of the bleeding risks associated with ibrutinib. One group performed a medication review of 96 CLL patients beginning ibrutinib and found that 64% of the patients were concurrently taking medications that increased the risk of ibrutinib toxicity, including CYP3A4 inhibitors carbamazepine, rifampin and rifabutin . When beginning ibrutinib, 9% of patients were taking an anticoagulant and 30% were on aspirin .…”
Section: Are Providers Conscious Of Bleeding Risk?mentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data describing physician and patient awareness of the bleeding risks associated with ibrutinib. One group performed a medication review of 96 CLL patients beginning ibrutinib and found that 64% of the patients were concurrently taking medications that increased the risk of ibrutinib toxicity, including CYP3A4 inhibitors carbamazepine, rifampin and rifabutin . When beginning ibrutinib, 9% of patients were taking an anticoagulant and 30% were on aspirin .…”
Section: Are Providers Conscious Of Bleeding Risk?mentioning
confidence: 99%
“…One group performed a medication review of 96 CLL patients beginning ibrutinib and found that 64% of the patients were concurrently taking medications that increased the risk of ibrutinib toxicity, including CYP3A4 inhibitors carbamazepine, rifampin and rifabutin . When beginning ibrutinib, 9% of patients were taking an anticoagulant and 30% were on aspirin . The data showed that 10% of the patients had clinically significant bleeding, with 4% (four patients, one on enoxaparin, two on an SSRI and one on a NSAID) requiring hospitalization .…”
Section: Are Providers Conscious Of Bleeding Risk?mentioning
confidence: 99%
“…Major bleeding was classified according to the Common Terminology Criteria for Adverse Events and included the following: (1) grade $3 (n 5 8), [1][2][3]15,16,28,30,31 (2) grade $2 (n 5 3), 4,26,29 (3) reason for drug discontinuation (n 5 2), 5,27 and (4) bleeding requiring hospitalization (n 5 1). 24 In addition, 3 studies did not report a definition of major bleeding; one of these studies 17 reported 10 events, including 1 resulting in death and 3 leading to drug discontinuation. In the 4 RCTs reporting on major bleeding, 1,3,6 (Figure 2).…”
Section: Major Bleedingmentioning
confidence: 99%
“…Thirteen articles reported on the incidence of overall bleeding 6,8,[15][16][17][18][19][20][21][22][23][24][25] with a pooled annual incidence of any bleeding of 20.8 per 100 patient-years (95% confidence interval [CI], 19.1-22.1) in ibrutinibtreated patients. Two RCTs 6,15 compared the incidence of overall bleeding between ibrutinib and an alternative therapy ( Figure 1).…”
Section: Overall Bleedingmentioning
confidence: 99%
“…Consumption of grapefruit and Seville oranges, as well as some supplements, also alter exposure of CYP3A4 metabolized drugs like ibrutinib. A recent study from the Mayo Clinic found that 64% of 118 CLL patients treated with ibrutinib were on medications that could increase toxicity through drug interactions, the majority of which were antiplatelet medications, but 18% were drug interactions through CYP3A 38 . Thus a careful medication review prior to ibrutinib prescription is important to avoid AEs like one reported with co-administration with the moderate CYP3A4 inhibitor verapamil 39 .…”
Section: Drug Interacti Onsmentioning
confidence: 99%